Outcome measures in trauma and orthopaedics: a guide to evaluating your practice. Issue 5 (October 2021) - Nisar, Sohail; Pandit, Hemant
Abstract: Improvements in health-related quality of life (HRQoL) are key in orthopaedic surgery, however appropriate, timely and meaningful measurement of HRQoL can be challenging. This paper provides an overview of the different types of commonly used outcome measures along with their characteristics and key properties used in trauma and orthopaedics. Orthopaedic surgeons are provided a basis to select the most appropriate measure to evaluate their clinical practice.